Lisunagara: Karya Kolaborasi Rebab dan Musik Digital - Gelar Seftiyana (Pascasarjana ISBI Bandung, 2020)
This paper is aimed to analyze a collaborative musical work between rebab and digital music. The analysis will be both on the content of the work and the media used, as well as the influence of technology on the composer’s work process involving their ideas. The work is entitled Lisunagara which means introducing fiddle to a broader realm. The research method used in this paper is a qualitative research method focusing on the description and analysis of the work. McLuhan’s theory of technological determination is considered in accordance with the object of this study where technology is able to influence human behavior. The results of this research prove that the fiddle cannot only be played in a convention (tradition) setting but can also be played through a digital approach so that it can be juxtaposed with other genres.Keywords: rebab, lisunagara, technological determinism, tradition, digital